KUALITAS MINAT BACA SISWA KELAS V DI SEKOLAH DASAR NEGERI 1 BUTON - Agus Sriwiani; La Jusu (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to determine the reading interest of fifth-grade students at SD Negeri 1 Buton. The research method used was observation, interviews, and documentation to collect qualitative data. The research results show that the reading interest of fifth-grade students at SD Negeri 1 Buton is still relatively low. The low reading interest of students is caused by several factors, both internal and external. Internal factors include a lack of reading habits from an early age, so students are not accustomed to spending time reading. Many students only read on the teacher's orders, not out of their own awareness. In addition, low reading skills are also a constraint, where some students still have difficulty understanding the reading material, causing them to feel bored and less interested in continuing to read. Meanwhile, external factors such as the role of the family also greatly influence the students' reading interest. Some students who have reading habits generally come from families who support and get them used to reading from an early age. However, many parents believe that the school is solely responsible for building their children's reading interest, so they do not provide sufficient encouragement at home. In conclusion, it can be said that the reading interest of fifth-grade students at SD Negeri 1 Buton is still low, caused by internal and external factors. Efforts have been made by the school, but the biggest challenge is the lack of support from the family. Therefore, close collaboration between teachers and parents is highly needed to build a strong reading culture in the students.